Comparison of short mechanical circulatory support in refractory cardiogenic shock: is selection of the devices appropriate?. (3rd May 2023) - Puerto, E; Vicent, L; Dominguez-Perez, L; Martin-Asenjo, R; Galan, D; Durante, A; Bruna, V; Davila, E; Bueno, H; Arribas-Ynsaurriaga, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The availability and accessibility to short-term mechanical circulatory support (ST-MCS) in each hospital may condition the choice of the device regardless of characteristics of patients with refractory cardiogenic shock (CS). Purposes: The objectives were to stratify the risk of patients with CS assisted with percutaneous or minimally invasive support (VA-ECMO, Impella CP and 5.0), to analyze whether the choice of ST-MCS was adequate according to the characteristics of the patient (severity, respiratory failure and right ventricular dysfunction) and differences in prognosis. Methods: Patients with CS requiring percutaneous or minimally invasive ST-MCS at a tertiary center from 2020 to August 2022 were prospectively included. Patients requiring immediately escalating from any device to VA-ECMO were included in the ECMO group for analysis. Early escalation from Impella CP to a more potent support (< 24 hours) was considered as inappropriate device selection. Bleeding was classified according to ELSO. Results: A total of 40 patients with CS were supported: 15 with VA- ECMO (37, 5%), 7 with Impella 5.0 (17, 5%) and 18 with Impella CP (45%). Impella 5.0 was mostly placed in patients with a less severe cardiogenic shock (SCAI-C 71, 4%, median lactate: 1, 2 mmol/l (1-1, 9), median VIS-score: 7, 3 (3, 1-26), median SOFA 5 (3, 75-7)), mainly due to decompensated chronic heart failure (71%) as a bridge to heart transplant (71%). VA-ECMO was mostly canulated after acute myocardial infarction (AMI)-related cardiogenic shock (46, 7%), mainly in patients with a profound shock (SCAI D 40% and E 53%, lactate 3(6-10, 25), VIS score 80 (40-80), SOFA 8 (6-11)). Impella CP was mainly inserted after AMI (77, 8%) in patients with intermediate severity (SCAI D (55, 6%), lactate 3, 9 (2, 3-5, 8), VIS 66 (29, 4-95), SOFA: 7 (6-8). No differences were found in the need for mechanical ventilation (p= 0, 426), nor the proportion of RV dysfunction (p= 0, 635). Upgrading from Impella CP to VA-ECMO was required in 7 patients (38%), 4 immediately in the cath-lab (22%) and 2 within the first 24 hours of support (11, 1%). Escalation from Impella CP to 5.0 was needed in 11, 1%, all after > 24 hours. Mortality during support was significantly higher in VA-ECMO group (40 vs 0 vs 11%; p=0, 041) and also in-hospital mortality (60 vs 14 vs 22%; p=0, 035), but no differences were found in first 24-hours mortality and 30-day mortality. There were not differences in complications (Table 1). Conclusions: Selection of first ST-MCS seems appropriate in 85% patients. Early escalation from Impella CP to VA-ECMO was necessary in 6 patients (15%, 33% Impella CP), probably implying inappropriate selection of first assistance probably due to faster and easier access to Impella CP. Higher in-hospital mortality and mortality during ST-MCS in VA-ECMO group, are probably explained by the greater severity of shock rather than the increase of complications during ST-MCS, which were similar among groups.